Shaping our varsities into icons - Abd Razak, Dzulkifli (2007)
IF there is any indicator as to how Malaysia would fare in the next 50 years, one just needs to look at the National Higher Education Strategic Plan launched by the prime minister just before the 50th Merdeka anniversary. Along with it is another compilation, the National Higher Education Action Plan (20072010). Both documents laid out a new pathway to the future, among them: • greater transparency in the selection of senior management; • development of a national lifelong learning policy; • exchange programmes where top students spend at least one semester abroad to enrich their learning experience; • industry attachment and secondment of academics to the private sector and viceversa; and, • regular audits on the quality of higher education institutions, including the advancement of research and innovation.